2016
DOI: 10.1111/apha.12710
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of myocardial stress resistance and signalling to voluntary activity and inactivity

Abstract: Data confirm the sensitive coupling of ischaemic tolerance to activity: voluntary running induces cardioprotection that dissipates within 1 week of inactivity yet recovers rapidly upon subsequent activity. While exercise in naïve animals induces a molecular profile characteristic of preconditioning/calorie restriction, only GSK3β and EGFR modulation consistently parallel activity- and inactivity-dependent ischaemic tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Physical stress (eg. wheel-running in naïve mice) induces cardioprotection via the same kinase signaling [55], and our recent unpublished findings suggest that psychological effects of environmental enrichment (placement of a locked running wheel in cages) may similarly boost infarct tolerance in caged mice, coupled with phospho-regulation of the same survival and stress kinases (see preliminary data in Fig. 3).…”
Section: Pre-ischemic Depressionmentioning
confidence: 81%
“…Physical stress (eg. wheel-running in naïve mice) induces cardioprotection via the same kinase signaling [55], and our recent unpublished findings suggest that psychological effects of environmental enrichment (placement of a locked running wheel in cages) may similarly boost infarct tolerance in caged mice, coupled with phospho-regulation of the same survival and stress kinases (see preliminary data in Fig. 3).…”
Section: Pre-ischemic Depressionmentioning
confidence: 81%
“…To more directly examine this topic, one study found that 2-weeks of running exercise in mice was associated with increased myocardial tolerance against ischemiareperfusion injury. 62 (Figure 2).…”
Section: Is Cardioprotection From Exercise Training Summative or Relamentioning
confidence: 99%
“…Myocardial Protein Expression Analyses. To examine changes in protein expression, phosphorylation, and localization, cardiac tissue fractions were assessed using western blotting as previously described (Budiono et al, 2016). Left ventricles were isolated and frozen in liquid N 2 before storage at 280°C.…”
Section: Methodsmentioning
confidence: 99%